The Cloud Ascends in Emerging Markets: Highlights of IEEE CCEM 2013. - Pingali, Gopal; Mohan, T.S. (Computer (00189162), 2014)
A review of the second annual IEEE International Conference on Cloud Computing in Emerging Markets, held last October in Bangalore, India, provides key insights about this important and growing domain.